A liberal peace? the problems and practices of peacebuilding - edited by Susanna Campbell (London Zed Books, 2011)
Moving beyond the binary argument between those who buy into the aims of creating liberal democratic states grounded in free markets and rule of law, and those who critique and oppose them, this timely and much-needed critical volume takes a fresh look at the liberal peace debate. In doing so, it examines the validity of this critique in contemporary peacebuilding and statebuilding practice through a multitude of case studies - from Afghanistan to Somalia, Sri Lanka to Kosovo. Going further, it investigates the underlying theoretical assumptions of liberal peacebuilding and statebuilding, as well as providing new theoretical propositions for understanding current interventions. Written by some of the most prominent scholars in the field, alongside several new scholars making cutting edge contributions, this is an essential contribution to a rapidly growing interdisciplinary area of study.
Includes index
Keywords: Peace-building; Neoliberalism; Intervention